The Role and Function of The Sumatra Toll Road in Supporting The Regional Economy of Lampung Province - Haris Haris; Rully Indrawan; Juliater Simarmata; Zulfa Fitri Ikatrinasari; Euis Saribanon; Okin Ringan Purba; Harry Purwoko (Dinasti International Journal of Education Management and Social Science, 2026)
This study examines the effects of the transportation and warehousing sector, tourism, and agriculture, forestry, and fisheries on economic growth, with Local Own-Source Revenue (PAD) serving as an intervening variable in regencies traversed by the Trans-Sumatra Toll Road (JTTS) in Lampung Province. The research covers six regencies—South Lampung, Central Lampung, Mesuji, Pesawaran, Tulang Bawang, and West Tulang Bawang—over the period 2020–2024, producing a balanced panel dataset of 30 observations. Panel data regression is applied using the Random Effects Model (REM), selected through Chow, Hausman, and Lagrange Multiplier tests. The mediating role of PAD is analyzed using the Sobel test. The results indicate that transportation and warehousing have a positive and statistically significant effect on economic growth. Similarly, agriculture, forestry, and fisheries also show a positive and significant direct effect on economic growth. In contrast, tourism exhibits a negative and significant direct effect, suggesting limited multiplier effects during the observation period. PAD does not have a statistically significant direct effect on economic growth. In the PAD model, only agriculture, forestry, and fisheries demonstrate a positive and significant influence, while transportation and warehousing and tourism do not significantly affect regional revenue. Mediation analysis reveals that PAD significantly mediates the relationship between transportation and warehousing and economic growth, as well as between agriculture and economic growth. However, PAD does not mediate the effect of tourism on economic growth. Overall, the findings suggest that the economic impact of the Trans-Sumatra Toll Road in Lampung Province operates primarily through improvements in logistics efficiency and enhanced agricultural distribution networks, with selective fiscal transmission effects. These results highlight the importance of integrating infrastructure development with sectoral upgrading and effective fiscal management to ensure sustainable and inclusive regional economic growth.